Gaya Kepemimpinan Kepala Sekolah dalam Meningkatkan Kinerja Guru SMA Nurul Hasanah Rangkasbitung Lebak - Chairulfalah, A. Machron (Fakultas Keguruan dan Ilmu Pendidikan Universitas Faletehan, 2022)
Teachers’ performance at SMA Nurul Hasanah Rangkasbitung Lebak are still considered less than expected, the teacher's performance is highly influenced by the leadership style and supervision abilities of the Islamic school principal. Therefore, this research was carried out to find out whether there was a contribution of the leadership style and the supervision abilities of the Islamic school principal to the teachers’ performance. This study used the School Action Research method, in which the research was conducted by supervisors in their own target areas. School Action Research was carried out through four stages, namely; action plan, action, observation, and reflection. The research subjects wewe 43 teachers of SMA Nurul Hasanah Rangkasbitung Lebak that was carried out from July to November 2022 with a total sample was 43 people. The statistical analysis used in this study was SPSS.This study showed: 1) the results of measuring the average teacher’s performance score was 118.44 and when compared to the ideal score of 180, the achievement level was 65.75%, which was categorized as the very high category; 2) The average score of the Islamic school principal’s leadership style was 95.45 and when compared to the ideal score of 130, the achievement level was 73.42%, which was categorized as the high category; 3). The average score for the supervision ability of the Islamic school principal was 90.04 and when compared to the ideal score of 135, the achievement level was 66.70%, which was categorized as the high category; 4) The contribution of the Islamic school principal’s leadership style to teacher’s performance had a regression analysis value of Ŷ = 78.35 + 0.42X1 which was included in regression significance; 5) The contribution of the supervision ability of the Islamic school principal to teacher’s performance had a regression analysis value of Ŷ = 57.05 + 0.68X2 which was included in regression significance; 6) The contribution of the Islamic school principal’s leadership style and the supervision ability of the Islamic school principal to teacher’s performance obtained a multiple regression equation of . It means that the regression coefficient was significant. The conclusions of this study were: 1) the performance was categorized as the very high category; 2) the leadership style of the Islamic school principal was categorized as the high category; 3) the supervision ability of the Islamic school principal categorized as the high category; 4) The contribution of the principal’s leadership style to teacher’s performance had significant value; 5) The contribution of the supervision ability of the Islamic school principal to teacher’s performance had significant value; 6) The contribution of leadership style and the supervision ability of the Islamic school principal to teacher’s performance was significant.